Characteristics and the trajectory of psychotropic medication use in general and antipsychotics in particular among adults with an intellectual disability who exhibit aggressive behaviour. (22nd January 2014) - Deb, S.; Unwin, G.; Deb, T.
Abstract Background A high proportion of adults with an intellectual disability (ID) are known to receive psychotropic medications for the management of aggressive behaviour in the absence of any psychiatric diagnosis. Despite this widespread use of psychotropic medication in general and antipsychotic medication in particular, no study has reported the trajectory of psychotropic medication use using a prospective design. Method We have prospectively studied a community, clinic‐based sample of 100 adults with ID and aggressive behaviour over a 6‐month period for use of psychotropic medication in general and antipsychotics in particular, and compared them with demographic, psychiatric and behavioural variables. Results Psychotropic medications were used for 89% of patients at baseline (T1) and 90% at 6 months' (T2) follow‐up. Risperidone was the most commonly used antipsychotic medication followed by chlorpromazine, haloperidol, olanzapine, zuclopenthixol and quetiapine. Other commonly used medications were SSRI antidepressants such as citalopram, paroxetine and fluoxetine followed by mood stabilisers such as carbamazepine and sodium valproate. Although in a high proportion of cases carbamazepine and sodium valproate were used to treat epilepsy per se. A high proportion (45%) received more than one (polypharmacy) psychotropic medication at T1; however, this proportion decreased slightly to 41% at T2. As for antipsychotic prescribing specifically, a similar proportion received them at T1 (75%) and T2 (73%), with polypharmacy of antipsychotics remaining similar at T1 (10%) and at T2 (9%). Twenty‐three per cent and 20% of patients received over 300 mg/day of chlorpromazine equivalent dose of antipsychotics at T1 and T2 respectively. However, there was an overall significant reduction in the severity of aggressive behaviour between T1 and T2. Higher doses of antipsychotic prescribing were positively correlated with more severe aggressive behaviour, physical aggression towards objects, self‐injurious behaviour and increasing age. There was no significant association with other demographic variables, physical health conditions or psychiatric diagnosis. Neither was there any significant correlation between mean aggression severity score change and antipsychotic daily dose change between T1 and T2. Conclusions To our knowledge, this is the first ever comprehensive follow‐up study of use of psychotropic medications in general but antipsychotics in particular over a 6‐month period in adults with ID and aggressive behaviour, in a clinic‐based community setting which also compared the trajectory of severity of aggressive behaviour with that of antipsychotic medication dose. Our study shows that not only the use of psychotropic medication is common among adults with ID who attend psychiatric clinics for aggressive behaviour, the use of polypharmacy of psychotropic medications in general and high dose of antipsychotics in particular are equally prevalent. However, in some cases two antipsychotics may have been prescribed simultaneously as the psychiatrist is in the process of switching from one to another.